Pacific Island countries: In search of a trade strategy - Hong Chen; Lanieta Rauqeuqe; Shiu Raj Singh; Yiqun Wu; Yongzheng Yang (Journal of Banking and Financial Economics (JBFE), 2019)
This paper examines the role of international trade for economic prosperity in Pacific island countries (PICs), discusses their comparative advantage, and explores the potential for trade, and tourism in particular, to serve as a locomotive for inclusive economic growth. We find the trade performance in PICs has been generally weak over the past decade, with the exception of resource-rich countries. Small country size and remoteness from global economic centers may have contributed to this relatively poor performance. Using the gravity models to analyze the determinants of merchandise trade and tourism in PICs, we find tourism in these countries faces more favorable conditions for growth than goods exports. Further, we place our analysis in the context of the eastward shift of global economic gravity, focusing on emerging Asia as a source of demand for resource-based goods and services. We argue that the emergence of Asia as a dynamic global economic region presents PICs with an unprecedented opportunity to develop trade, particularly tourism, although traditional markets will remain important for a long time to come. Moreover, if stronger synergies can be established between tourism, agriculture, and fisheries, Pacific island countries stand a better chance to improve broad-based growth.
Keywords: F6; 330; Pacific island countries; trade; tourism; agriculture; inclusive growth